Pendampingan Strategi Pemasaran Digital Berbasis Media Sosial untuk Meningkatkan Visibilitas dan Sukses Usaha Masyarakat Urban - Mahliza, Febrina; Rosdiana, Riska; Pernamasari, Rieke (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this community service activity is to improve the understanding and skills of MSME actors in urban areas, especially in Meruya Utara Village. The methods used in this mentoring activity are socialization and training. The results of this mentoring activity show an increase in participants' knowledge of the importance of digital marketing and a high interest in implementing social media in their business activities. Participants also showed interest in developing their business accounts more professionally. The discussion of this activity emphasizes that social media-based digital marketing training is very relevant and needed by urban MSME actors. This activity contributes to encouraging business sustainability by expanding market reach and increasing competitiveness through more modern and effective marketing strategies.